Effect of Extreme Consumption of Clove on the Morphology of Mice and Liver Tissue (Indian Journal of Forensic Medicine & Toxicology, 2021)
Introduction: Flavors are one of the main materials used in the world kitchens. Therefore, we must research their harms in the service of society. Objective: This study aimed to investigate the effect of too much cloves consumption on the morphological and histological structure of the mice liver. It is important to have a clear view of the excitements that play a major role in damaging organs. Methodology: About 20 mice were used. I was orally (1g) to ginger for 50 days. that anesthetization, separating the liver, fixing by formalin, using the routine method to preparation block and sectioning (5um) then coloured with H&E. Results: symptoms was decrease in weight and signs of dehydration and hair loss,. the liver appearance of severe congestion with a dark red colour, accompanied by bleeding and the appearance of necrosis in the liver. Microscopy indicated a loss of the normal structure of the liver tissue. The sections also showed the emergence of the stages of programmed death of cells.Conclusion: We concluded that consuming spices in large quantities will lead to toxic liver toxicity, but it is not dangerous.
Keywords: Clove, Liver, Mice, Morphology, Tissue